Does inhibitory control training reduce weight and caloric intake in adults with overweight and obesity? A pre-registered, randomized controlled event-related potential (ERP) study. (January 2021) - Carbine, Kaylie A.; Muir, Alexandra M.; Allen, Whitney D.; LeCheminant, James D.; Baldwin, Scott A.; Jensen, Chad D.; Kirwan, C. Brock; Larson, Michael J.
Abstract: A cognitive intervention that may reduce weight and caloric intake is inhibitory control training (ICT; having individuals repeatedly withhold dominant responses to unhealthy food images). We conducted a randomized controlled trial where 100 individuals with overweight or obesity were assigned to complete a generic ( n  = 48) or food-specific ICT ( n  = 52) training four times per week for four weeks. Weight and caloric intake were obtained at baseline, four-weeks, and 12-weeks. Participants also completed high-calorie and neutral go/no-go tasks while N2 event-related potential (ERP) data, a neural indicator of inhibitory control, was measured at all visits. Results from mixed model analyses indicate that neither weight, caloric intake, nor N2 ERP component amplitude towards high-calorie foods changed at post-testing or at the 12-week follow up. Regression analyses suggest that individuals with smaller N2 difference amplitudes to food may show greater weight loss and reductions in caloric intake after a generic ICT, while individuals with larger N2 difference amplitudes to food may show greater weight loss and reductions in caloric intake after a food-specific ICT. Overall, multiple food-specific or generic ICT sessions over the course of a four-week period do not affect overall weight loss, caloric intake, or N2 ERP amplitude. Highlights: Four ICT sessions over four weeks do not affect weight or food intake. Four ICT sessions over four weeks do not affect N2 amplitude to high-calorie foods. Generic ICT may be more effective for individuals with lower inhibition. Food-specific ICT may be more effective for individuals with higher inhibition. Generic and food-specific ICT decreases appetitive drive to consume food.